2020
DOI: 10.1038/s41586-020-2254-4
|View full text |Cite
|
Sign up to set email alerts
|

Liquid flow and control without solid walls

Abstract: Solid walls become increasingly important when miniaturizing fluidic circuitry to the micron scale or smaller. 1 They limit achievable flow-rates due to friction and high pressure drop, and are plagued by fouling 2 . Approaches to reduce the wall interactions have been explored using hydrophobic coatings 3,4 , liquid-infused porous surfaces [4][5][6] , nanoparticle surfactant jamming 7 , changing the surface electronic structure 8 , electrowetting 9,10 , surface tension pinning 11,12 , and atomically flat chan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 44 publications
1
64
0
Order By: Relevance
“…circuits on surfaces without the functionalization of particles. Meanwhile, magnetofluids, liquid with magnetic particles, could directionally migrate and quickly reconfigure the topography under magnetic fields, and thus are helpful in manipulating ferrofluid droplets without contact, [18] and in creating passages in channels to conduct flow control, [19] etc. Microfluidics concerns the manipulation of small volumes of fluid samples through the network of channels that have dimensions less than tens and hundreds of micrometers.…”
Section: Liquid With Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…circuits on surfaces without the functionalization of particles. Meanwhile, magnetofluids, liquid with magnetic particles, could directionally migrate and quickly reconfigure the topography under magnetic fields, and thus are helpful in manipulating ferrofluid droplets without contact, [18] and in creating passages in channels to conduct flow control, [19] etc. Microfluidics concerns the manipulation of small volumes of fluid samples through the network of channels that have dimensions less than tens and hundreds of micrometers.…”
Section: Liquid With Particlesmentioning
confidence: 99%
“…To realize various flow control functions such as valving, pumping, splitting, and merging, Hermans et al guided aqueous liquid channels with immiscible magnetic liquid, both of which are stabilized by a quadrupolar magnetic field in 2020. [19] Such fluidic channels featured with liquid-liquid interfaces while being supported by magnetic particles show near-frictionless, self-healing, antifouling, and non-clogging properties. It is demonstrated that the magnetostaltic pumping method provides a new platform to transport delicate liquids such as whole human blood with no need for high pressure, and could also be applied for microfluidic circuitry.…”
Section: Liquid With Particlesmentioning
confidence: 99%
“…Recently, Dunne et al developed a flow technique based on magnetic flow freeing themselves from the excessive hydrostatic pressure stemming from wall friction. [17] Nonetheless, such microfluidic networks with increasing complexity and length still result in higher hydrostatic pressures, which, in turn, could weaken the stability of the flow rate and the oil/water interface, when both fluids are in direct contact. The situation becomes increasingly challenging with a developing viscosity difference between the two phases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27,28 ] Other solid‐wall‐free strategies to confine liquids include embedding of water into a matrix of viscous poly(dimethylsiloxane) oil, [ 29,30 ] water–oil emulsions in microfluidic devices, [ 31,32 ] and aqueous channels held by immiscible magnetic liquid barriers. [ 33 ] With these strategies, however, only water can be confined. Here we demonstrate that on small scales the mechanical stability of water confined on a hydrophilic surface can be high enough to act as a solid‐like wall, capable of containing another liquid.…”
Section: Introductionmentioning
confidence: 99%